Pemberdayaan Ekonomi Kreatif Masyarakat Melalui Pelatihan Pembuatan Sabun Mandi di Kelurahan Tangkerang Barat Kota Pekanbaru - Ratna, Ihkwani; Nasrah , Hidayati (Jurnal Pengabdian Masyarakat Isei, 2023)
This community service is carried out to support the creativity of the people in Pekanbaru City in utilizing free time to increase family income. The activity took the form of soap production training followed by entrepreneurial skills for the soap product. The training participants were housewives who live in the West Tangkerang sub-district as many as 50 people. With this training activity it is hoped that the community in the West Tangkerang sub-district of Pekanbaru City will be able to produce liquid soap along with entrepreneurial skills. The expected impact is increasing welfare through independently fulfilling the need for liquid soap as well as efforts to empower the economy for local residents.